The Tuan Guru Tradition of Nahdlatul Wathan in Pesantren - Supratman Muslim; Suprapto Suprapto; Jamaluddin Jamaluddin (Graduate Program of Pontianak Institute of Islamic Studies, 2022)
Pesantren (Islamic Boarding Schools) is a religious educational institution that has long history in Indonesia. Pesatren has an important role in producing religious figures, including kyai (an expert of Islamic teachings) or tuan guru (grand teacher). However, this role began to fade as many secular educational institutions emerged due to modernization and globalization, and at the same time pesantren began to change a lot to adapt to this new system. This study aims to explore the role of the Ma’had Dar Al-Qur’an wa Al-Hadith Nahdlatul Wathan (MDQH NW) Islamic boarding school in maintaining the tuan guru (grand teacher) tradition, and the strategies used to maintain this tradition. This study used a qualitative method with data collected through techniques of participatory observation, in-depth interviews and documentation. The results indicate that the MDQH NW has a significant contribution in maintaining the tuan guru tradition. This is demonstrated by the pattern of education and all institutional activities oriented to the pesantren culture with the study of the al-Mu’tabarah book with the halaqah system. The strategies include strengthening traditional education, strengthening socio-religious relations, and strengthening Islamic da’wah. Continuity is also seen in the social relations built with the masyayikh (internal quality assurance) at Madrasah Shaulatiyah Makkah. Changes also occurred at the MDQH NW in Pancor regarding the duration of studies, especially for the talibat (female students) who previously took 3 years then extended to 4 years, which is the same duration as the tullab (male students). However, the MDQH NW Islamic Boarding School in Anjani still maintains the rule that has become the legacy of its founders, namely three years for the talibat and four the tullab.